Applications of Maqasid al-Shari’ah and Maslahah in Islamic Banking practices: an analysis - Al-Mubarak, Tawfique; Osmani, Noor Mohammad (2010)
Islamic Banking system has developed more than thirty years ago. Throughout its history, beside its successes, it assumed much controversies and criticism in its run to win the hearts of the Muslim clients. Established with the objective of providing an interest-free (riba-free) banking service, it has so far been criticized to open several other back-doors to riba-based transactions, despite its immense success in creating an alternative to the conventional banking system. This paper aims to analyze some of the contemporary Islamic Banking products and practices in the light of maslahah and maqasid al-Shari’ah in order to propose a better banking system for the Muslims. It also shows how the preference of ‘macro- maqasid’ over the ‘micro-maqasid’ is not a perfect justification for many such Islamic Banking practices. The paper suggests that Bai’ al-‘Inah, along with few other contemporary practices like Bai’ Bithaman Aajil (BBA) and ijarah Sukuk needs to be thoroughly revised before being offered as a riba-free product, as it does not comply with the maqasid of Islamic Economic and Banking principles – economic development, social wellbeing, individual freedom and equality, elimination of injustice and poverty, etc.